Nonendoscopic Signs of Esophageal Varices in Individuals with Chronic Liver Disease - Megha Majumder; SK Nasim; Kausik Bhar; Jotideb Mukhopadhyay (Bengal Physician Journal)
Introduction: Cirrhosis is a long-term liver disease frequently linked to increased portal venous pressure, which can result in the formation of esophageal varices (EV). Among the numerous complications arising from portal hypertension, EV are the most prevalent clinical symptom. The rupture of these varices is the most severe and potentially fatal consequence of portal hypertension. Esophagogastroduodenoscopy is commonly used for the diagnosis and continuous monitoring of EV. Nonetheless, in many developing nations, regular endoscopic surveillance for cirrhosis patients poses a considerable challenge due to constrained healthcare resources. Objective: Evaluation of the accuracy of noninvasive tests in diagnosing EV in patients with cirrhosis. Materials and methods: This study is a descriptive cross-sectional analysis that included 100 patients newly diagnosed with cirrhosis who had no prior incidents of variceal bleeding. Various nonendoscopic parameters were assessed, such as platelet count, coagulation profile, and abdominal ultrasonography. Additionally, the platelet count-to-spleen diameter ratio was used to detect and grade EV in these liver cirrhosis patients, with confirmation achieved through endoscopy. Results: In patients with liver cirrhosis, the presence of EV was significantly linked to anemia, ascites, encephalopathy, splenomegaly, a reduced platelet count, increased prothrombin time, decreased serum albumin, average spleen size, a larger portal vein diameter, and a notably lower platelet count-to-spleen diameter ratio in those with large EV. Conclusions: The findings of the current study indicate that certain parameters are closely linked to the severity of varices and may be beneficial for their early detection and subsequent management.